2021
DOI: 10.3390/foods10020379
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaved and Extruded Legumes as a Source of Bioactive Phytochemicals: A Review

Abstract: Legumes have been consumed since ancient times all over the world due to their easy cultivation and availability as a low-cost food. Nowadays, it is well known that pulses are also a good source of bioactive phytochemicals that play an important role in the health and well-being of humans. Pulses are mainly consumed after processing to soften cotyledons and to improve their nutritive and sensorial characteristics. However, processing affects not only their nutritive constituents, but also their bioactive compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 150 publications
(384 reference statements)
0
34
0
Order By: Relevance
“…Extrusion is a versatile, high-temperature–short-time technology that allows the production of fully cooked, low-moisture, and shelf-stable food products [ 1 , 2 ]. Nowadays, extrusion is one of the most interesting technological processes used by the food industry for the fabrication of a variety of food products since this technology is suitable for the development of value-added products, from pulses and other grains, including gluten-free snacks, with functional properties, high nutritional value, and attractive organoleptic characteristics [ 3 , 4 , 5 , 6 ]. This is relevant as snack-type products have currently become a significant part of the diet of many people around the world, particularly children, and these food products represent an excellent vehicle to improve consumer’s health.…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion is a versatile, high-temperature–short-time technology that allows the production of fully cooked, low-moisture, and shelf-stable food products [ 1 , 2 ]. Nowadays, extrusion is one of the most interesting technological processes used by the food industry for the fabrication of a variety of food products since this technology is suitable for the development of value-added products, from pulses and other grains, including gluten-free snacks, with functional properties, high nutritional value, and attractive organoleptic characteristics [ 3 , 4 , 5 , 6 ]. This is relevant as snack-type products have currently become a significant part of the diet of many people around the world, particularly children, and these food products represent an excellent vehicle to improve consumer’s health.…”
Section: Introductionmentioning
confidence: 99%
“…Pulses ( Fabaceae ) are an interesting alternative to animal proteins. They are rich in proteins, unsaturated fatty acids, and bioactive compounds and thus present nutritional and environmental benefits [ 1 , 2 , 3 , 4 , 5 ]. Moreover, they offer functional properties for food applications [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to know that the traditional Japanese diet contains about 420 protease inhibitor units/day. It has been reported as well as that consumption of purified protease inhibitor at 25–800 CIU per day during a period of 12 weeks promoted protective effects against cancer disease development and a dose over 2000 CIU/day did not cause health problem in human ( Pedrosa et al, 2021 ; Muzquiz et al, 2012 ; Carbonaro, 2011 ; Singh et al, 2017 ). It has been also reported that a diet with 1% sodium phytate added can control hypercholestrolaemia and atherosclerosis and it can reduce the risk of colon cancer in the same time it can improve irritable bowel syndrome ( Barman et al, 2018 ; Schlemmer et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%